Pengaruh Role Stressor terhadap Turnover Intention dengan Job Satisfaction sebagai Variabel Intervening di Perusahaan Bongkar Muat X Surabaya - Satya Mandiri, Avedo (Universitas Nahdlatul Ulama Surabaya, 2020)
Stress can be sourced from several factors or commonly known as stressors. Operational employee has been identified as a job that has high stress level. Hang-yue(20056) states that an employee who is under stress due to sources of stress can have an impact on decreasing job satisfaction. This can also lead to increased turnover intention. The purpose of this study was to determine the effect of role stressor on turnover intention directly nor indirectly. This study using quantitative approach and nonprobability sampling technique with saturated sampling of 40 employees from operational division’s stevedoring company in Surabaya. Data analysis techniques using path analysis. The results showed that there was a significant negative effect between role stressor and turover intention directly nor indirectly